First nesting account and breeding biology of "gould's Inca" (Coeligena torquata omissa) in Manu National Park, Peru (2016)
We present the first detailed nesting biology information for the highland Andean hummingbird Gould's Inca (Coeligena torquata omissa) at 2,200-3,000 m in Manu National Park, SE Peru. We found nine mossy cup-shaped nests lined with red fern scales containing nestlings or 1-2 synchronously hatching eggs. We obtained 17 days of internal nest temperatures from one nest, which exhibited wide circadian variation (range = 14.9-36.2 °C). We show that C. t. omissa meets the challenges of life and incubation at high altitudes by undertaking numerous (20.3 ± 0.4 trips/morning, range = 14-27) and short morning off-bouts (5.2 ± 0.2 min, range = 1-24 min). In the morning, the focal bird warmed the nest 1.7 times faster than in the afternoon where incubation bouts are long (17.8 ± 0.6 min, range = 4-56) and less frequent (10.2 ± 0.3 trips/afternoon). Incubation off-bout frequency and durations were not influenced by external temperature, suggesting strong nest insulation. On-bout durations increased with external temperature most strongly in the cold mornings. Short off-bouts and long on-bouts yielded high attentiveness (70.2%). One nestling fledged after 23 days. The eggs measured 15.2 ± 0.4 mm by 9.3 ± 0.3 mm and weighed 0.75 ± 0.03 g (n = 12). The small mossy cup nest was 81.9 ± 5.9 mm by 75.8 ± 4.4 mm wide and 73.1 ± 6.7 mm high. The inner cup was 45.7 ± 3.0 mm long by 45.6 ± 4.1 mm wide and 30.9 ± 2.5 mm deep (n = 8). Compared to C. t. torquata, we found a smaller egg width, higher nest placement and different nest substrate, but confirmed similarities in many aspects of nesting strategies.